2013
DOI: 10.1002/clc.22086
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic Bioimpedance and Brain Natriuretic Peptide Assessment for Prognostic Stratification of Outpatients With Chronic Systolic Heart Failure

Abstract: Background: In patients with chronic heart failure, physical evaluation and clinical judgment may be inadequate for prognostic stratification. Hypothesis: Information obtained with simple bedside tests would be helpful in patient management. Methods: We report on 142 outpatients with systolic heart failure seen at our heart failure unit from 2007 to 2010 (ages 69.4 ± 8.9 years; ejection fraction [EF] 30.6 ± 6.1%; 43% with implanted defibrillators and/or resynchronization devices). At their first visit, we ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…BNP and NT-pro-BNP are markers of severity and prognosis of acute coronary syndrome and heart failure. [ 19 ]…”
Section: Introductionmentioning
confidence: 99%
“…BNP and NT-pro-BNP are markers of severity and prognosis of acute coronary syndrome and heart failure. [ 19 ]…”
Section: Introductionmentioning
confidence: 99%
“…Evidently lower mortality (2.1%) was observed in the group with BNP values < 450 pg/ml and the TFC < 40/kΩ, while in patients with BNP values ≥ 450 pg/ml and TFC ≥ 40/kΩ, the mortality was 46.5%. The use of this type of diagnosis during the 1st visit may help ensure better treatment of the patient by enabling implementation of an appropriate therapeutic strategy [14].…”
Section: Methodological Principlesmentioning
confidence: 99%
“…A feasibility study using the BIM sensor for home TM has been conducted, where it was shown to predict episodes of hospitalization for worsening HF [SCHAUERTE P, UNPUBLISHED DATA]. Multimodal assessments of CHF patients with natriuretic peptides, BIM and clinical evaluation have been shown to identify those with thoracic congestion and more adverse prognosis [26]. This modality of lung congestion monitoring holds great promise in providing 'snap-shot' measurements, which may be easily performed at home on a daily basis, to provide crucial information about patients at risk of 'danger zone congestion status.'…”
Section: Spectroscopic Bioimpedancementioning
confidence: 99%